Men and Masculinity in Men’s Stylish Lifestyle Magazine - Jerome, Collin (k@ta: A Biannual Publication on the Study of Language and Literature, 2009)
This paper discusses qualitative findings from a series of focus group discussions with six adult Malaysian men, aged 24-34, on the representation of men and masculinity in Men’s Folio, a stylish lifestyle men’s magazine. It highlights the extent to which the language used in the magazine’s editorial content and advertisements that feature musculature images, fashion and style, and feminized grooming products and practices that have diversed impacts on the respondents’ notions of a modern male identity.